Work and sleep quality in railway employees: an actigraphy study. Issue 1 (2nd January 2020) - Gerhardt, Christin; Kottwitz, Maria Undine; Lüdin, Tarsia Jana; Gabriel, Dominique; Elfering, Achim
Abstract: This actigraphy study tests whether daily work stressors (time pressure, social stressors), work resources (control, social support) and mental detachment from work predict sleep quality, when controlling for demands and control after work. Fifty-two railway employees participated during five consecutive workdays by completing diary questionnaires and wearing an actigraphy device. The results confirmed that social stressors from supervisors predicted more frequent sleep fragmentation and lower sleep efficiency the following night. Higher levels of daily time control at work predicted shorter sleep-onset latency and better self-reported sleep quality. Leisure time control as a covariate turned out to be a private resource, followed by fewer awakenings the following night. Detachment after work related negatively to social stressors and time pressure at work but was unrelated to indicators of sleep quality; detachment after work neither mediated nor moderated the relationship between social stressors from supervisors and sleep quality. Work redesign to increase time control and reduce social stressors is recommended to preserve daily recovery in railway employees. Practitioner summary: Sleep is important to renew health- and safety-related resources in railway employees. This diary and actigraphy study shows that higher daily work stressors were antecedents of lower sleep quality the following night, while more time control was followed by better sleep quality. Work redesign could promote health and safety by improving sleep quality.